Minimally invasive techniques and indocyanine angiography in anterior abdominal wall reconstruction after multiple laparotomies - Tomasz Buczek; Wiesław Tarnowski; Marcin Kuriata; Maciej Śmietański (Videosurgery and Other Miniinvasive Techniques)
Anterior abdominal wall reconstruction surgery in patients who have undergone multiple laparotomies is associated with a high risk of complications. For this reason, minimally invasive surgery techniques are used to avoid abdominal compartment syndrome, to enhance wound healing and to reduce postoperative pain and blood loss. This paper presents a case of a patient who was admitted to the Department of General Surgery in Puck Hospital as a result of extensive anterior abdominal wall deformation with an end descending colostomy. A single-stage procedure was performed: specifically, digestive tract reconstruction followed by anterior abdominal wall reconstruction using intraoperative angiography of indocyanine green in infrared light.